The genus Setodes Rambur (Trichoptera, Leptoceridae) in Japan - Katsuma, Nobuyuki (Zootaxa, 2018)
This report presents a revision of the Japanese species of the genus Setodes Rambur (Leptoceridae), and confirms 8 species. Among these are 3 new species: Setodes chirotheca sp. nov., distributed from Hokkaido to eastern Honshu; S. moritai sp. nov., distributed from central to western Honshu and Shikoku; and S. pseudofurcatulus sp. nov., from western Honshu. Additionally, several species are re-described: S. hinumaensis Katsuma 2009, S. ujiensis (Akagi 1960), S. minutus Tsuda 1942b, S. shirasensis Kobayashi 1984, and S. argentatus Matsumura 1907. One species, S. curviseta Kobayashi 1959 was originally described from Kyushu and is now synonymized with S. minutus. The larva, pupa, and case of S. hinumaensis are described for the first time.